EFFECTIVENESS OF COCONUT WATER CONSUMPTION ON BLOOD PRESSURE - Faozi, Ekan; Fadlilah, Siti; Syukur, Bambang Abdul; Susanto, Rachmat (Jurnal Keperawatan Respati Yogyakarta, 2022)
Blood pressure as a circulatory system is influenced by psychosocial (stress), genetic, age, sex, nutritional status, and lifestyle (diet, lack of fiber consumption, smoking, lack of physical activity). 30 ml of young coconut water containing 61 mg of potassium, 5.45 mg of sodium, and 1.3 mg of sugar can affect changes in blood pressure. This study aims to determine the effect of consumption of young coconut water on blood pressure nursing students at Respati University Yogyakarta. This type of research is a quasi-experiment with the design of a pre and post-test nonequivalent control group. The sampling technique used simple random sampling, as many as 36 samples. Test using T-test Paired and Wilcoxon. The results of the analysis of systolic and diastolic blood pressure pretest-posttest in the control group obtained p-value of 0.121 and 0.361. The systolic blood pressure analysis and diastole pre-post test results in the experimental group obtained p-values ​​of 0.030 and 0.194. The posttest systolic and diastolic blood pressure analysis in the control and experimental groups obtained p-values ​​of 0.021 and 0.371, which concluded that there was an effect of consumption of coconut water on systolic blood pressure in nursing students. Keywords: Blood Pressure; Diastolic; Systolic; Young Coconut Water